MBA 2016-17 Business Plan_Light Box - Sonawane, Neelam (2017)
Our start up, Light Box, aims to create efficiency for real estate developers and property-seekers of the residential sector in the city of Mumbai in India by creating an immersive, imaginative and interactive virtual reality (VR) experience of the un-built apartment.